A New Model for Quantitative In Vivo Microscopic Analysis of Thrombus Formation and Vascular Recanalisation: The Ear of the Hairless (hr/hr) Mouse - Roesken, Frank; Ruecker, Martin; Vollmar, Brigitte; Boeckel, Nicole; Morgenstern, Eberhard; Menger, Michael D (Thrombosis and Haemostasis, 1997)
The alteration of rheological blood properties as well as deterioration of vascular perfusion conditions and cell-cell interactions are major determinants of thrombus formation. Herein, we present an experimental model which allows for quantitative in vivo microscopic analysis of these determinants during both thrombus formation and vascular recanalisation. The model does not require surgical preparation procedures, and enables for repeated analysis of identical microvessels over time periods of days or months, respectively. After i.v. administration of FITC-dextran thrombus formation was induced photochemically by light exposure to individual arterioles and venules of the ear of ten anaesthetised hairless mice. In venules, epiillumination induced rapid thrombus formation with first platelet deposition after 0.59 ± 0.04 min and complete vessel occlusion within 7.48 ±1.31 min. After a 24-h time period, 75% of the thrombosed venules were found recanalised. Marked leukocyte-endothelial cell interaction in those venules indicated persistent endothelial cell activation and/or injury, even after an observation period of 7 days. In arterioles, epi-illumination provoked vasomotion, while thrombus formation was significantly (p <0.05) delayed with first platelet deposition after 2.32 ± 0.22 min and complete vessel occlusion within 20.07 ±3.84 min. Strikingly, only one of the investigated arterioles was found recanalised after 24 h, which, however, did not show leukocyte-endothelial cell interaction. Heparin (300 U/kg, i.v.) effectively counteracted the process of thrombus formation in this model, including both first platelet deposition and vessel occlusion. We conclude that the model of the ear of the hairless mouse allows for distinct in vivo analysis of arteriolar and venular thrombus formation/ recanalisation, and, thus, represents an interesting tool for the study of novel antithrombotic and thrombolytic strategies, respectively.